Tailoring sintering step allows high performance for solid oxide fuel cells prepared by a tri-layer co-firing process. (September 2017) - Dai, Hailu; Shafi, Shahid P.; He, Shoucheng; Bi, Lei
Graphical abstract: Highlights: A step sintering strategy was proposed to improve the performance for SOFCs. Cathode microstructure was optimized by using the step sintering strategy. The step sintering strategy allowed a reduced polarization resistance. SOFCs prepared by the tri-layer co-firing method showed superior performance. Abstract: A step sintering strategy is proposed to sinter the solid oxide fuel cell fabricated by the tri-layer co-firing method. Compared with the conventional sintering strategy for the tri-layer co-firing method which has to compromise the cathode performance with electrolyte densification, tailoring sintering steps allows the densification of electrolyte and the formation of an optimal cathode microstructure simultaneously, leading to a much enhanced electrochemical performance. The impedance analysis suggests that the desirable cathode microstructure achieved through the step sintering favors the cathode reaction, attaining a polarization resistance as low as 0.022 Ω cm 2 at 700 °C which is about one third of that for the cell sintered by a conventional method. The cell performance reaches 455 mW cm −2 at 700 °C by employing the step sintering strategy, while the cell performance measured is only 289 mW cm −2 with the conventional sintering approach.